PENGARUH UNREAL ENGINE DALAM PERKEMBANGAN DUNIA GAME - Mungky Hendriyani; Agung Dharma Saputra; Febrianto Herlambang (JEIS: Jurnal Elektro dan Informatika Swadharma, 2022)
The development of games industries today is speedy and has become more modern. The game company must develop their game to the next level, for example not long-ago Epic Games company release their new engine. The engine used for making the game can be used for 3D modeling as well. Unreal Engine 5 provided terrific graphics and more features than an older version of Unreal Engine. Epic Games company provided their engine free for all or open-source which can be used by anyone for free. Unreal Engine can be more useful for the game developer or 3D modeling. Without a doubt that Unreal Engine 5 by Epic Games can bring a new era to the game. A lot of developer wants to create a more powerful engine than Unreal Engine 5 but for now, there is no new engine that can beat Unreal Engine 5. For example, Frostbite engine by DICE adds more updates to catch up with Unreal Engine 5